Hypomethylated Pollen Bypasses the Interploidy Hybridization Barrier in Arabidopsis . Issue 9 (12th September 2014) - Schatlowski, Nicole; Wolff, Philip; Santos-González, Juan; Schoft, Vera; Siretskiy, Alexey; Scott, Rod; Tamaru, Hisashi; Köhler, Claudia
Abstract : Paternal hypomethylation can bypass the interploidy hybridization barrier by alleviating the requirement for the epigenetic Polycomb Repressive Complex 2 (PRC2) in the endosperm. The hypomethylated pollen genome causes de novo CHG methylation directed to FIS-PRC2 target genes, suggesting that different epigenetic modifications can functionally substitute for each other. Abstract: Plants of different ploidy levels are separated by a strong postzygotic hybridization barrier that is established in the endosperm. Deregulated parent-of-origin specific genes cause the response to interploidy hybridizations, revealing an epigenetic basis of this phenomenon. In this study, we present evidence that paternal hypomethylation can bypass the interploidy hybridization barrier by alleviating the requirement for the Polycomb Repressive Complex 2 (PRC2) in the endosperm. PRC2 epigenetically regulates gene expression by applying methylation marks on histone H3. Bypass of the barrier is mediated by suppressed expression of imprinted genes. We show that the hypomethylated pollen genome causes de novo CHG methylation directed to FIS-PRC2 target genes, suggesting that different epigenetic modifications can functionally substitute for each other. Our work presents a method for the generation of viable triploids, providing an impressive example of the potential of epigenome manipulations for plant breeding.